2014
DOI: 10.1016/j.jchf.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand Syndrome in Patients With a Centrifugal or Axial Continuous Flow Left Ventricular Assist Device

Abstract: AvWS developed in all patients after centrifugal or axial flow pump implantation. Different patterns of AvWS were seen between the devices as well as individually. However, the complication rates after implantation were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(151 citation statements)
references
References 16 publications
6
144
0
1
Order By: Relevance
“…All rotary pumps induce avWS and all patients are affected to some degree; however, not all patients experience clinical bleeding. Indeed, one study found that there was no correlation between the degree of decrease in HMWMs and the tendency for bleeding in patients with CF LVAD (4 had a history of bleeding events, all of whom had impaired ristocetin-induced platelet aggregation (6). The authors found that this was a consequence of both avWS and attenuated platelet function.…”
Section: Strike 1: Cf Lvad Induced Bleeding Diathesismentioning
confidence: 99%
“…All rotary pumps induce avWS and all patients are affected to some degree; however, not all patients experience clinical bleeding. Indeed, one study found that there was no correlation between the degree of decrease in HMWMs and the tendency for bleeding in patients with CF LVAD (4 had a history of bleeding events, all of whom had impaired ristocetin-induced platelet aggregation (6). The authors found that this was a consequence of both avWS and attenuated platelet function.…”
Section: Strike 1: Cf Lvad Induced Bleeding Diathesismentioning
confidence: 99%
“…12 Nearly all patients treated with MCS develop acquired von Willebrand syndrome with loss of high molecular weight von Willebrand factor multimers (Table 1). [13][14][15][16][17][18][19] The exception may be the Syncardia TAH, as three patients with normal von Willebrand multimers after TAH implantation have been reported. 20 The severity of acquired von Willebrand syndrome is similar between the HeartMate II and HVAD devices.…”
Section: Effects Of Mcs On the Hematologic Systemmentioning
confidence: 99%
“…20 The severity of acquired von Willebrand syndrome is similar between the HeartMate II and HVAD devices. 14 The association between GI bleeding and acquired von Willebrand syndrome is debated as the severity of the acquired von Willebrand syndrome is not associated with an increased risk for GI bleeding. 14 Additional investigation is underway to understand the pathophysiology of GI bleeding in LVAD patients and the role of von Willebrand factor in angiogenesis.…”
Section: Effects Of Mcs On the Hematologic Systemmentioning
confidence: 99%
“…Also, a recent study by Meyers et al compared low-shear centrifugal devices and axial flow devices and found no difference in the impact on vWF, suggesting mechanisms beyond shear. 53 While shear forces create changes in platelet function and erythrocyte lysis, they likely have no specific link to the lack of pulse pressure. Most studies with CF pumps have shown platelet activation, but a recent study in patients with HeartMate II devices showed no changes in platelet function (measured by soluble P-selectin and CD40L) irrespective of duration of support.…”
Section: Hematologic Functionmentioning
confidence: 99%